Kurikulum Ulya di Pondok Pesantren Darul Ulum Al-Burhan Palembang - Ahmad Zainuri; Muhammad Adil; Ibrahim (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Islamic boarding schools are faith-based educational institutions in Indonesia. Islamic boarding school education has developed in Indonesia, the majority of people adhere to Islam. The purpose of this study was to determine the independent curriculum of learning at the Ponpes Darul Ulum Al-Burhan cottage. This research uses qualitative methods, with data collection techniques in the form of observation, interviews, and documentation. The results of the study stated that the independent learning curriculum of Ponpes Ponpes Darul Ulum Al-Burhan has not been implemented. Ponpes implemented the 2013 curriculum for formal education, while for the Ponpes curriculum itself, Ponpes has its own curriculum which is the hallmark of Ponpes Ponpes Darul Ulum Al-Burhan. Some of the books that are studied for students, including the book of Jalalain. Then it relates to the process of learning the book, ustadz and ustazah who teach tahfidz Al-quran